Poster: We Are Well: Our well-being superpower (leaves) - Geraldine Burke; Priscilla Pettengell; Chris Hanger (2023)
The poster, We Are Well: Our well-being superpower (leaves) is part of a suite of posters that document the 'We Are Well: Intergenerational art-moving-well-being' project. It showcases a series of gum leaves harvested from a local tree and drawn on to depict well-being assets through words and pattern. Poster text: Look what we bring to the learning. Look what I bring to the group. We are artists/researchers/teachers with amazing superpowers to share. Poster Authors: Geraldine Burke, Priscilla Pettengell, Chris Hanger Photography: Geraldine Burke, Melanie Attard, Aislinn Lalor, Megan Adams, Chris Hanger Project Acknowledgments: The We Are Well: Intergenerational art-moving-well-being research team Dr Geraldine Burke, Assoc Prof Megan Adams, Assoc Prof Laura Alfrey, Dr Aislinn Lalor, Prof Keith Hill, and Priscilla Pettengell with artists : Nikki Browne, Bidjara artist and educator, and First Nations Learning and Programs Manager, McClelland Sculpture Park and Gallery, Aunty Karan Kent, Bidjara Elder. Founder of Yimba Yumba — in sync with nature through the art of sharing Wayapa Wuurrk, Kylie Colemane, Darug, and Wiradjuri First Nations consultant, artist, and educator. Founder of Your Green Prescription, Kursty Colemane, Darug, and Wiradjuri First Nations knowledge holder, artist, and educator.